Impact of two different exercise programs on persistent cancer-related fatigue and physical fitness - Reis, Fabiana; Cecatto, Rebeca Boltes; Brito, Christina May Moran de; Hoff, Paulo Marcelo Gehm; Battistella, Linamara Rizzo (Acta Fisiátrica, 2012)
Cancer-related fatigue is a common symptom in patients with cancer, which is experienced by 70% to 100% of these patients and brings some impairment of physical and mental performance, hinders their working or carrying out regular daily activities, and hence results in a substantial reduction of the quality of life. Physical exercise has consistently been identified as a central element of rehabilitation for many chronic diseases like cancer, and increasing evidence supports the contention that physical activity is a valuable intervention that can be utilized in conjunction with conventional therapies during CRF treatment. Objective: The aim of this study was to assess the impact of a program of physical exercise on fatigue levels and physical performance of cancer patients. Method: A consecutive series of 44 adult patients with neoplastic disease (solid or hematological), with a medical diagnosis of fatigue, who were enrolled in an oncological treatment, with the ability to walk and willing to enter a rehabilitation program of exercise for at least 4 consecutive months. The exercise program was performed two times per week, each session lasting one hour and consisting of aerobic, resistance, and flexibility exercises. The protocol was divided into aerobic exercise and resistance training combined with aerobic exercise. The patients were evaluated with two assessments: one prior to their beginning the exercise program and other at the end of the four-month program. In both assessments the patients completed the Revised Piper Fatigue Scale and the six-minute walk test. The primary outcome of change over baseline and after 16 weeks in PFS-R score and six-minute walk test were compared using a two sample two-sided t-test for both groups. Alpha level was set at p < 0.05. Results: After 16 weeks, the patients who participated in the aerobic or the combined exercise program reported significantly higher levels of physical functioning (6-minute walking test, p = 0.0009 and p = 0.001, respectively) and significantly lower fatigue (PFS-R, p = 0.003 and p = 0.002, respectively) than at the beginning the exercise program. Conclusion: The results of patients who underwent aerobic or aerobic + anaerobic exercise showed statistically significant improvement of physical performance and of fatigue. Data from this study corroborates with the literature showing that exercise programs with aerobic or resistance exercises are an effective strategy for the treatment of fatigue. The results of this study confirm that physical exercise could be useful in rehabilitation of cancer survivors, especially for fatigued patients.